Infective Endocarditis: New Challenges in a Classic Disease - Cuervo, Guillermo; Hernández-Meneses, Marta; Falces, Carles; Quintana, Eduard; Vidal, Bárbara; Marco, Francesc; Perissinotti, Andrés; Carratalà, Jordi; Miro, Jose M.; The Hospital Clinic and the Hospital of Bellvitge Endocarditis Team Investigators (Seminars in Respiratory and Critical Care Medicine, 2022)
Infective endocarditis is a relatively rare, but deadly infection, with an overall mortality of around 20% in most series. Clinical manifestations have evolved in response to significant epidemiological shifts in industrialized nations, with a move toward a nosocomial or health-care-related pattern, in older patients, with more episodes associated with prostheses and/or intravascular electronic devices and a predominance of staphylococcal and enterococcal etiology.Diagnosis is often challenging and is based on the conjunction of clinical, microbiological, and imaging information, with notable progress in recent years in the accuracy of echocardiographic data, coupled with the recent emergence of other useful imaging techniques such as cardiac computed tomography (CT) and nuclear medicine tools, particularly 18F-fluorodeoxyglucose positron emission/CT.The choice of an appropriate treatment for each specific case is complex, both in terms of the selection of the appropriate agent and doses and durations of therapy as well as the possibility of using combined bactericidal antibiotic regimens in the initial phase and finalizing treatment at home in patients with good evolution with outpatient oral or parenteral antimicrobial therapies programs. A relevant proportion of patients will also require valve surgery during the active phase of treatment, the timing of which is extremely difficult to define. For all the above, the management of infective endocarditis requires a close collaboration of multidisciplinary endocarditis teams.
Keywords: infective endocarditis; epidemiology; pathogenesis; diagnostic criteria; cardiac surgery; antimicrobial treatment; outpatient parenteral antibiotic therapy (OPAT); antibiotic prophylaxis